2017
DOI: 10.3389/fped.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Risk and Respiratory Complications in Patients with Esophageal Atresia

Abstract: Chronic, long-term respiratory morbidity (CRM) is common in patients with a history of repaired congenital esophageal atresia, typically associated with tracheoesophageal fistula (EA/TEF). EA/TEF patients are at high risk of having aspiration, and retrospective studies have associated CRM with both recurrent aspiration and atopy. However, studies evaluating the association between CRM in this population and either aspiration or atopy have reported conflicting results. Furthermore, CRM in this population may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…However, salivary pepsin did not correlate with other respiratory symptoms, pulmonary function testing results or LRSQ scores. Although this could be due to the small sample size of the current study, a more likely explanation may be the multi-factorial etiology for respiratory morbidity in EA patients with reflux aspiration being only one of the causes (2).…”
Section: Salivary Pepsinmentioning
confidence: 83%
See 2 more Smart Citations
“…However, salivary pepsin did not correlate with other respiratory symptoms, pulmonary function testing results or LRSQ scores. Although this could be due to the small sample size of the current study, a more likely explanation may be the multi-factorial etiology for respiratory morbidity in EA patients with reflux aspiration being only one of the causes (2).…”
Section: Salivary Pepsinmentioning
confidence: 83%
“…Esophageal atresia associated with tracheo-esophageal fistula (EA), is commonly associated with long-term gastrointestinal and respiratory morbidity including gastroesophageal reflux disease (GERD), esophageal strictures, recurrent respiratory tract infections, chronic cough and asthma (1). GERD resulting in reflux aspiration is one of the causes for respiratory complications in this cohort (2). GERD occurs in 22-45% of EA patients (3).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we did not investigate interrelationships between oral aspiration and gastroesophageal reflux, although both conditions may predispose children to LRTI, and both conditions may occur concurrently. 21 However, recent research has suggested that use of proton pump inhibitors in children with aspiration may increase the risk of all-cause hospitalization. 22 We did not track concurrent medication use.…”
Section: Genetic Causes Of Laryngeal Cleft Include 22q Deletion Syndrmentioning
confidence: 99%
“…Feeding problems, which occur in 79% of infants [12], increase the risk of airway aspiration and might be responsible for chronic respiratory morbidity, such as recurrent pneumonia, asthma, and bronchiolitis [13].…”
Section: Introductionmentioning
confidence: 99%